Stigma and mental health problems in an Indian context. Perceptions of people with mental disorders in urban, rural and tribal areas of Kerala. (March 2023) - Raghavan, Raghu; Brown, Brian; Horne, Francesca; Kumar, Sanjana; Parameswaran, Uma; Ali, Ameer B; Raghu, Ardra; Wilson, Amanda; Svirydzenka, Nadia; Venkateswaran, Chitra; Kumar, Manoj; Kamal, Sreedevi R; et al.
Background: The concept of stigma has been widely used to understand patterns of discrimination and negative ideas surrounding people with mental health problems, yet we know little of the specific nuances of how this might operate beyond the 'Global North'. Aim: This paper aims to explore the notion of stigma in an Indian context by considering the lived experience of patients, carers and community members. Methods: A sample of 204 participants, representing mental health patients, informal carers and community members was recruited from urban and rural areas in Kerala, India. Participants took part in interviews where they were encouraged to talk about their experiences of mental ill health, attitudes towards these problems, barriers encountered and sources of support. Results: Experiences akin to the experience of stigma in Europe and the United States were elicited but there were important local dimensions specific to the Indian context. The difficulties faced by people with diagnoses of mental disorders in finding marriage partners was seen as an important problem, leading to marriage proposals being refused in some cases, and secrecy on the part of those with mental health problems. Rather than the 'self-stigma' identified in the US, participants were more likely to see this as a collective problem in that it could reflect badly on the family group as a whole rather than just the sufferer. Conclusions: In the Indian context, the idioms of stigma emphasised impairments in marriage eligibility and the implications for the family group rather than just the self.